Effect of Pseuduvaria macrophylla in attenuating hyperglycemia mediated oxidative stress and inflammatory response in STZ-nicotinamide induced diabetic rats by upregulating insulin secretion and glucose transporter-1, 2 and 4 proteins expression - Taha, Hairin; Arya, Aditya; Khan, Ataul Karim; Shahid, Nayiar; Noordin, Mohammed Ibrahim; Mohan, Syam (Elsevier, 2018)
Pseuduvaria macrophylla (Family: Annonaceae) is commonly used as medicinal plant in Malaysia. A recent study with the Pseuduvaria species showed antioxidant and antidiabetic effects. This study aimed to ascertain antidiabetic potential of methanolic extract of Pseuduvaria macrophylla bark (PM) using streptozotocin-nicotinamide induced diabetic rat models. Various phytochemical and biochemical properties of the plant have been evaluated. The results showed that the extract has potentially normalized the elevated blood glucose levels by upregulating the insulin and C-peptide levels and alleviated oxidative stress by improving glutathione (GSH) and reducing lipid peroxidation (LPO) in the diabetic rats. In addition, PM has drastically downregulated the levels of pro-inflammatory cytokines and transforming growth factor beta-1 (TGF-β1). Histopathological examination of the pancreas in PM treated diabetic rats showed significant recovery of the pancreatic structural degeneration and thus reflected the protective role of PM against peroxidation damage by a rise in insulin level as evidenced by the immunohistochemistry study. The improved expressions of GLUT-1, GLUT-2 and GLUT-4 further confirmed the restoration of β-cell mass by PM. Interestingly, the findings demonstrated the antioxidant, anti-inflammatory and antihyperglycemic potential of PM which may provide future lead for the management of type-2 diabetes.